Automatización de riego y fertilización mediante una red inalámbrica de sensores en la ESPAM MFL - Macías Ramírez, Manuel de Jesús (2019)
The purpose of the present work was to implement, in an automated way, an irrigation and fertilization control system by using a wireless sensor network, within the facilities of the MFL ESPAM, in such a way that the use of water and fertilizer resources will be optimized. In order to achieve the specified objective, EDER methodology was used, which provides clear and relevant processes in the performing of technological infrastructure projects. In the first step of the used methodology, the existing devices in the market for automation were analyzed, selecting the Arduino boards to carry out the proposed project, as well as XBee devices that serve for the data transmission between the nodes. Subsequently, the system design was carried out, which includes humidity sensors and solenoid valves, as well as a rechargeable solar battery for the power supply of the node. Then, the implementation of the system was performed, according to the considered design and materials. The respective operation tests were performed, both for functionality as well as on battery life duration, obtaining that the estimated autonomy of the battery allows it to work several days at the node (at least 108.7h) even in the extreme case of not receiving sunlight. At the end, a low cost system was obtained, which could perform the autonomous irrigation and fertilization of plants, according to soil conditions parameters, previously configured, with good battery life duration in wireless sensor nodes.